2011
DOI: 10.1071/ea08303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of Lifetimewool on sheep producers

Abstract: Abstract. Lifetimewool was a national project that began in 2001 to develop profitable ewe feeding and management guidelines for wool producers across southern Australia. By 2005, the project included communication and adoption activities. Rigorous communication, adoption and evaluation plans were used to maintain focus on its objectives and to measure impacts. Evaluation was an integral part of the project's development and allowed the project to gain a clear idea of its impact. The project aimed to influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 7 publications
0
20
1
1
Order By: Relevance
“…This undoubtedly contributed to over 3000 producers attributing changed practice to Lifetimewool (Jones et al 2011). The condition score models and worksheets were the most recognised tools (Table 2).…”
Section: Producersmentioning
confidence: 99%
See 1 more Smart Citation
“…This undoubtedly contributed to over 3000 producers attributing changed practice to Lifetimewool (Jones et al 2011). The condition score models and worksheets were the most recognised tools (Table 2).…”
Section: Producersmentioning
confidence: 99%
“…Eighty-four consultants and extensionists responded to an on-line survey to provide feedback on the use and value of the tools to their business. In addition, other information about respondents' agreement with the key messages and their preparedness to recommend the guidelines and tools to clients was collected and is reported by Jones et al (2011). A telephone survey of 1353 producers from across Australia was also conducted to assess the use of tools.…”
Section: The Process For Developing Messages and Adoption Approachesmentioning
confidence: 99%
“…The responses to these questions were weighted to reflect the likely impact of each innovation on their livestock enterprise and the aggregate score was used to allocate each producer to a market segment according to their innovativeness (Rogers 2003). This approach determined the level of innovativeness of the participants before the training and whether the level of innovativeness of a producer influenced their degree of practice change as a result of participating in the program (Jones et al 2011). These categories of innovativeness were then split into two groups, with 'innovators' and 'early adopters' as one group and 'early majority', 'late majority' and 'laggards' as the other.…”
Section: Survey Designmentioning
confidence: 99%
“…This proved to be the most effective of the approaches tested. Jones et al (2011) reported the results from a national survey which interviewed a random sample of 1200 sheep producers in 2008 and found that 90% of producers that had participated in Lifetime Ewe Management reported changing practices due to their involvement in the program, compared with 12% in the total survey population.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys show that few farmers routinely weigh ewes to manage their nutrition as they believe this practice has little value, is time consuming and/or expensive (Jones et al 2011). In addition, measurement of maternal liveweight must be corrected for gut fill, wool growth, conceptus and moisture (CSIRO 2007).…”
Section: Introductionmentioning
confidence: 99%